Uji Kemurnian Ekstrak Galaktomanan Biji Durian (Durio zibethinus L.) dengan Metode Luff Schoorl - Nilsya Febrika Zebua; Sumardi; Suprianto; Alizha Aisyah (Yayasan Penelitian dan Inovasi Sumatera, 2022)
Introduction: Galactomannan is found in the endosperm of seeds in the Fabaceae family, for example durian seeds (Durio zibethinus L). Galactomannan is a natural polysaccharide as an additional ingredient. Objective: The research aims to determine the Galactomannan content in Durian seeds isolated by chromatography and to determine the Galactomannan content in Durian seeds using the Luff Schoorl method. Methods: The research was carried out by extracting galactomannan from Durian seeds using distilled water by heating them for 5 minutes. Purification was carried out using paper chromatography with various variations of mobile phases, namely BEW (Butanol: Ethanol: Water), BAW (Butanol: Acetic acid: Water), Glacial acetic acid 10%, Glacial acetic acid 50%, HCl 10%, HCl 20% and Thin layer chromatography with the mobile phase n-Hexane: Ethylacetate at varying ratios of 3:7 and 7:3. Purity testing is carried out using the Luff Scroorl method. Results: Extraction of 500 g of durian seeds produces 1,8% Galactomannan. The levels before and after inversion using the Luff Schoorl method were respectively 8.0131 and 7.0679 mg/mg. Conclusion: Galactomannan can be obtained from extracting durian seeds and its inverse using the Luff Scroorl method.